Spray formation of middle distillates for autothermal reforming. (6th July 2017) - Peters, R.; Pasel, J.; Samsun, R.C.; Scharf, F.; Tschauder, A.; Müller, M.; Müller, A.; Beer, M.; Stolten, D.
Abstract: The reforming of diesel and diesel-like fuels plays a central role in the development of fuel cell systems for on-board power supplies. The vaporization of the fuel via a spray formation and the subsequent mixture with water vapor and air determine the quality of the reforming process, as is shown in this paper. By using a high quality nozzle residual hydrocarbons were below 25 ppmV during the reforming of standard diesel. Through the use of a fuel injector in pulsed operation, the load range was able to be increased from 1:1.67 to 1:6. Spray pattern analyses were conducted using a high-speed camera. The formation of the spray pattern lasted 1.5–2 ms. The testing of a fast-closing magnetic valve manufactured by GSR Ventiltechnik was carried out on the autothermal reformer (ATR) type AH2. It exist not any direct influence of the pulsed operation on hydrogen production. Graphical abstract: Highlights: A fast-closing magnetic valve for pulse operation enabled a load range 20%–100%. Formation of the fuel spray pattern lasted 1.5–2 ms, breakdown 3.2 ms. Spray pattern dissolved without any irregularities and without droplet formation. Residual hydrocarbons were reduced from 200 ppmV to below 25 by a high-quality nozzle.